Aktivitas antelmintik ekstrak herba meniran (Phyllanthus niruri) terhadap Paramphistomum spp. - Safriyana, Baiq Ihda Nanda; Hidayati, Agriana Rosmalina; Pratama, Iman Surya (Sasambo Journal of Pharmacy, 2024)
Phyllanthus niruri is traditionally used to treat intestinal worms. The content of flavonoids in Phyllanthus niruri has the potential as an anthelmintic. The aims of study are to identify flavonoid compounds of the ethanolic extract of Phyllanthus niruri and determine the anthelmintic activity against Paramphistomum spp. Paramphistomum spp. grouped into positive control (Albendazole 10% w/v), negative control (CMC-Na 0.5% w/v), ethanolic extract of Phyllanthus niruri 1.25%, 2.5%, and 5% w/v. For 5 hours, the time and quantity of dead worms were counted every 15 minutes. The average time of death and percentage of worm mortality were then calculate. Differences in average time of death were analyzed with Kruskal-Wallis and Mann Whitney. The results of the test tube and TLC showed the content of flavonoid compounds. Percentage of mortality of Paramphistomum spp. obtained by 100%. Average death time of Paramphistomum spp. at 50, 275, 155, 140, and 115 minutes respectively. Ethanolic extract of Phyllanthus niruri contained flavonoid compounds and has anthelmintic activity with an optimum concentration of 5% w/v although lower than Albendazole 10% w/v (p<0.05).